Pengetahuan ibu hamil tentang kehamilan resiko tinggi di wilayah kerja Puskesmas Cepogo Kabupaten Boyolali - Lestari, Ayu Eka; Nurrohmah, Anjar (Universitas Muhammadiyah Magelang, 2021)
Background: High risk pregnancy causes some complications, one of them is death among pregnant women. Recently, the number of mother’s death was increasing. One of the causes is lack of knowledge among pregnant women. Aim: The aim of this study was to describe the level of knowledge of pregnant women in Puskesmas Cepogo related to high risk pregnancy. Method: This study was a descriptive study. The research population was 250 repondents. The sampling method was proportionate stratified random sampling and the sample of this study was 71 respondents. This study was using questionnaire to measure the variables. Univariate analysis was using in this study. Results: This study found that among pregnant women in The Puskesmas Cepogo, the majority (49 repondents/ 69.0%) had lower knowledge about high risk pregnancy. Most of the pregnant women was younger than 20 years and got basic education (SD/SMP). For the income, most of the pregnant women only got less than 1 million rupiah per month. Conclusion: In the Puskesmas Cepogo, the level of knowledge among pregnant women related to the high risk pregnancy was lower.